Timing of prophylactic antibiotic use during elective caesarean section: a meta-analysis of randomised controlled trials - Shi-Fu Hu; Ying-Ying Wang; Yan-Qing Wu; Qiong Yu (IMR Press, 2021)
Perioperative antibiotic therapy is recommended to reduce the incidence of infection after caesarean section. However, the optimal timing of prophylactic antibiotic administration in such cases remains controversial. With this meta-analysis, we aimed to evaluate the safety and efficacy of prophylactic antibiotic therapy before skin incision versus after umbilical cord clamping in patients undergoing elective caesarean section. We searched the PubMed, EMBASE, Cochrane Library and Web of Science databases for randomised controlled trials (RCTs) published between January 1, 2000 and July 1, 2020. The 1101 initially identified references were narrowed to 10 RCTs involving 5020 women for the final analysis. Briefly, we determined that prophylactic antibiotic therapy before skin incision not only reduced the incidence of postpartum endometritis (relative risk (RR), 0.56; 95% confidence interval (CI), 0.34-0.92; P = 0.02), but also decreased the rate of total infectious morbidity (RR, 0.79; 95% CI, 0.64-0.98; P = 0.03) when compared to antibiotic therapy after umbilical cord clipping. However, the two timings of antibiotic administration did not lead to significant differences in the incidence of wound infection (RR, 0.73; 95% CI, 0.54-1.00; P = 0.05), maternal febrile morbidity (RR, 1.20; 95% CI, 0.67-2.14; P = 0.54), neonatal sepsis (RR = 0.65; 95% CI, 0.37-1.13; P = 0.13), septic workup (RR, 0.89; 95% CI, 0.67-1.18; P = 1.00) or neonatal intensive care unit admission (RR, 0.87; 95% CI, 0.69-1.09; P = 0.23). In conclusion, the prophylactic administration of antibiotics before a skin incision is made for an elective caesarean section can significantly decrease the incidence of total infectious morbidity and postpartum endometritis.